2022
DOI: 10.1051/0004-6361/202142311
|View full text |Cite
|
Sign up to set email alerts
|

Long-period Ap stars discovered with TESS data: The northern ecliptic hemisphere

Abstract: The rotation periods of the magnetic Ap stars span five to six orders of magnitude. While it is well established that period differentiation must have taken place at the pre-main sequence stage, the physical processes that lead to it remain elusive. The existence of Ap stars that have rotation periods of tens to hundreds of years is particularly intriguing, and their study represents a promising avenue to gain additional insight into the origin and evolution of rotation in Ap stars. Historically, almost all th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Not included at the time of this writing are the studies of Bowman et al (2018), Sikora et al (2019a), David-Uraz et al (2019), Bernhard et al (2020), and Mathys et al (2020bMathys et al ( , 2022. Except for two stars from the list of Mathys et al (2022) 4 , there are no matches between the samples of these studies and our sample. The VSX has data for only 64 out of the 782 objects presented here.…”
Section: Presentation Of Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Not included at the time of this writing are the studies of Bowman et al (2018), Sikora et al (2019a), David-Uraz et al (2019), Bernhard et al (2020), and Mathys et al (2020bMathys et al ( , 2022. Except for two stars from the list of Mathys et al (2022) 4 , there are no matches between the samples of these studies and our sample. The VSX has data for only 64 out of the 782 objects presented here.…”
Section: Presentation Of Resultsmentioning
confidence: 92%
“…It contains the results of most relevant papers dealing with the periods of ACV variables (including more recent studies, such as Paunzen & Maitzen 1998, Wraight et al 2012, Bernhard et al 2015a,b, 2021and Hümmerich et al 2016). Not included at the time of this writing are the studies of Bowman et al (2018), Sikora et al (2019a), David-Uraz et al (2019), Bernhard et al (2020), and Mathys et al (2020bMathys et al ( , 2022. Except for two stars from the list of Mathys et al (2022) 4 , there are no matches between the samples of these studies and our sample.…”
Section: Presentation Of Resultsmentioning
confidence: 99%
“…While the rate of occurrence of roAp stars among ssrAp stars, which may reach ∼20%, is considerably higher than the fraction of roAp stars among all Ap stars (Mathys et al 2022), roAp stars seldom belong to binary systems (Hubrig et al 2000;Schöller et al 2012;Hey et al 2019). Such binary systems are wide: the shortest orbital period that has been accurately determined for a pair containing an roAp star, HD 42659, is 93 d .2 (Hartmann & Hatzes 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Originally, this classification referred to stars whose spectra resemble those of Am stars but show an abnormally strong Sr ii λ 4077 Å line. However, as noted by North (1987), a specific definition of the criteria that allow one to distinguish F str λ 4077 stars from Am, Ap Sr, or λ Boo stars was missing at the time 1 . This left some ambiguity in the classification.…”
Section: Introductionmentioning
confidence: 99%
“…Among these 72 stars, four stars (TIC 2934856, TIC 239801694, TIC 291258469, and TIC 434372218) do not show detectable rotation features. Mathys et al (2020Mathys et al ( , 2022 found a total of 127 super slowly rotating Ap stars (ssrAp stars) that have long rotation periods so that no obvious rotational variability is seen in one TESS sector, or more. Among our four stars without rotation features detected, TIC 239801694 was identified as an ssrAp star candidate in Mathys et al (2022), and the other three stars may also be candidates, or their rotation inclination angles are quite small.…”
Section: Rotation Featuresmentioning
confidence: 99%